"Em briga de marido e mulher, se mete a colher, sim!" Avaliação da rede de atendimento às mulheres em situação de violência doméstica em São Gonçalo do Amarante-CE - Machado, Natália Moreira (2024)
This study aims to evaluate the work developed by the network of assistance to women in situations of domestic violence in the municipality of São Gonçalo do Amarante-CE (SGA-CE) based on the National Policy to Combat Violence against Women and anchored in the critical-dialectical evaluation of Maria Ozanira Silva e Silva. Specifically, it was of interest to explain the institutional trajectory of this network; describe how the articulation between the participating agencies occurs and explain the dynamics of the execution of the actions developed by the equipment of the assistance network based on the perception of the professionals, managers and users of these services. For this, we used bibliographic, field and documentary research, as well as interviews and questionnaires, carried out between July and September 2024 and involving different subjects: 04 users, 03 managers and 08 professionals. The analysis was content analysis. From this perspective, based on the participants' statements, it can be observed that SGA-CE generally has a considerably established flow of care for women in situations of domestic violence and that professionals and users are reasonably familiar with the agencies that make up this network. It can be inferred that the equipment in this network is composed of professionals from various areas, which we consider necessary for comprehensive care for women, given that violence is multifaceted and that it has a considerable number of public servants, which can help to prevent turnover of technical teams and thus help to establish bonds with users. Thus, based on the participants' statements, positive aspects of the functioning of this network were identified, such as, for example, quality and welcoming care to avoid revictimization. In contrast, points for improvement were also mentioned, such as the decentralization of facilities (to increase access), especially for women in rural areas, and access to public transportation for the population. Therefore, for women to be able to break the cycle of violence, feel welcomed, not revictimized and have full access to services, it is necessary not only to create several agencies, legislation and trained professionals, but also to coordinate this protection network.